Minimálbér-paradoxon - versenyzőpiacon? Egy gondolatkísérlet tanulságai - István R. Gábor (Hungarian Academy of Sciences, Institute of Economics, 2009)
– In the conventional textbook demand-supply model of competitive labour markets, introduction of a minimum wage above the market-clearing level must reduce employment. Empirical findings suggest, however, that this might not always be the case, which appears to be most readily explained by monopsonistic competition in the labour market. The thought experiment reported here takes an alternative root: it interprets the phenomenon of "minimum-wage paradox" as an eventuality in a competitive labour market with friction.
Keywords: E20; E30; J38; 330; minimum wage and employment; minimum wage paradox; friction and search in the labour market; disequilibrium-induced alterations in demand and supply; wage rigidity; Arbeitsuche; Arbeitsmarkt; Erwerbstätigkeit; Mindestlohn; Lohnrigidität